PENGARUH INTENSITAS PENGGUNAAN TIKTOK AKUN @CLAHAYES SEBAGAI SARANA EDUKASI TERHADAP PEMENUHAN KEBUTUHAN INFORMASI KESEHATAN DIET PARA FOLLOWERS - Apriyana, Lala; Pane, Ivanina Zuhdi; Harahap, Halomoan; Vardiansyah, Dani (Magister Komunikasi Universitas Sultan Ageng Tirtayasa, 2023)
Currently, Tiktok is one of the social media that continues to grow and is favoured by large audience. Not only uploading dance videos like when they first appeared, Tiktok now also makes it easier for users to provide and disseminate information. One of the accounts that utilizes the social media Tiktok as a medium for disseminating health information is the @clahayes account. The purpose of this study was to determine the intensity of using the Tiktok account @clahayes, to find out the fulfilment of information needs, and to find out how much influence from the intensity of using the Tiktok account @clahayes. The account has served as a communicator who releases messages of education on fulfilment of the health information needs of diet followers (communicant). The theory used in this study is Uses and Gratifications, with a quantitative approach using a survey method. Questionnaire as a data collection method was distributed to Tiktok @clahayes followers who are in total 100 after calculated using Slovin formula. This study uses purposive sampling technique. The results indicate that the frequency distribution on the variable Intensity of Use of Tiktok (X) are included in the high category, which is equal to 55%, while the results of the frequency distribution on the information needs variable (Y) are included in the high category, which is 100%. It can be concluded that the higher the intensity of using Tiktok, the higher the fulfilment of information needs. The results of the simple linear regression test in this study had a significance value of 0.000 <0.05. Thus, Ho is rejected and Ha is accepted. The effect on the variable intensity of use of Tiktok (X) has a percentage of influence of 35.4% on information needs (Y).Keywords: Intensity of Social Media Use, Information Needs, Tiktok